2014
DOI: 10.1186/s12909-014-0239-4
|View full text |Cite
|
Sign up to set email alerts
|

A proposed core curriculum for dental English education in Japan

Abstract: BackgroundGlobalization of the professions has become a necessity among schools and universities across the world. It has affected the medical and dental professions in terms of curriculum design and student and patient needs. In Japan, where medicine and dentistry are taught mainly in the Japanese language, profession-based courses in English, known as Medical English and Dental English, have been integrated into the existing curriculum among its 83 medical and 29 dental schools. Unfortunately, there is neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 8 publications
1
23
0
1
Order By: Relevance
“…If these dental students could gain more confidence in their abilities, they might decide to study abroad. Regarding language skills, conducting dental programs in both English and Japanese or teaching English vocabulary related to dentistry might be helpful, as national board examinations and the dental care system in Japan are organised in Japanese. Moreover, it is important for students who want to study abroad to receive detailed information about the skills and knowledge required to succeed in such an endeavour, as well as support from their school in finding suitable exchange programs.…”
Section: Discussionmentioning
confidence: 99%
“…If these dental students could gain more confidence in their abilities, they might decide to study abroad. Regarding language skills, conducting dental programs in both English and Japanese or teaching English vocabulary related to dentistry might be helpful, as national board examinations and the dental care system in Japan are organised in Japanese. Moreover, it is important for students who want to study abroad to receive detailed information about the skills and knowledge required to succeed in such an endeavour, as well as support from their school in finding suitable exchange programs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Japan's six-year undergraduate dentistry programme, only general English for academic purposes featured in the curriculum, and while some institutes did introduce special 'Dental English' training in their curricula, most students 'are unclear about what exactly constitutes Dental English' (Morse and Nakahara, 2001: 168). Since then, a core curriculum for dental English education has been proposed in Japan to offer more specific English training in medical and dental terminology and patient-and inter-and intra-professional interaction (Rodis, et al, 2014). Yet this Japanese example appears to be an isolated case, and there is still a lack of evidence in the literature regarding whether such training eventually leads to writing that appears to follow the rhetorical and attitudinal norms of the profession in which the students are to become enculturated, and whether training in writing leads to opportunities for learning about the discipline.…”
Section: Enculturation Into the Profession -English In The (Dentistrymentioning
confidence: 99%
“…Pro cient dental English ability can expand the students' horizons and explore more possibilities in the career. 5 Study showed that in non-English speaking country such as Japan, the competency and con dence in the English language could be one of the biggest obstacles for dental students to study abroad. 6 Poor English ability may limit the possibility of career path for the dental students.…”
Section: Future Expectation Of Dental English Education In Chinamentioning
confidence: 99%